Copper-catalyzed transformation of alkyl nitriles to N-arylacetamide using diaryliodonium salts. Issue 26 (28th April 2021) - Sallio, Romain; Payard, Pierre-Adrien; Pakulski, Paweł; Diachenko, Iryna; Fabre, Indira; Berteina-Raboin, Sabine; Colas, Cyril; Ciofini, Ilaria; Grimaud, Laurence; Gillaizeau, Isabelle
Abstract : In this study, a simple and efficient method for the copper-catalyzed redox-neutral transformation of alkyl nitriles using eco-friendly diaryliodonium salts and leading to N -arylacetamides was investigated. Abstract : This work reports a simple and efficient method for the copper-catalyzed redox-neutral transformation of alkyl nitriles using eco-friendly diaryliodonium salts and leading to N -arylacetamides. The method features high efficiency, broad substrate scope and good functional group tolerance.